An Analysis Of Moral Value In “Imperfect” Movie - Rita Harisma; Ayu Kusheilla Apriliana; Vivin Agustin (EDUTECH, 2023)
Today’s moral education is so important in view of the many moral cases that have taken place until bullying has affected psychological victims. This research discusses about the moral values of the characters in the “Imperfect” movie. The purpose of this research was to identify the types of moral values in “Imperfect” movie and to analyze the types of moral value that occur in “Imperfect” movie. The research was conducted by applying descriptive qualitative research. The data sources are taken from the entire “Imperfect” movie and the transcript in “Imperfect” movie which focuses on the use of moral values and the types of moral values. The findings of this research in “Imperfect” movie, found 12 types of moral values that occur in it. There were;4 data for responsibility, 16 data respect, 2 data for justice, 7 data for tolerance, 8 data for wisdom, 2 data for democracy, 7 data for altruism, 12 data for love and loyalty, 9 data for self- discipline, 6 data for courage, 7 data for help each other and 4 data for never give up. From this research, the researcher hope that after reading this research, the reader understands moral values.